1. Solve for y in the second equation by isolating the variable:
-2y = 11
y = -4
2. Substitute the value of y into the first equation:
-7x - 2(-4) = -13
-7x + 8 = -13
-7x = -21
x = 3
3. The solution to the system of equations is:
x = 3, y = -4
So, the solution to the system of equations by substitution is x = 3, y = -4.
Put the steps that are used to solve the following systems of equations by substitution. Answer Correctly.
-7x-2y= -13
- 2y = 11
:: y = -4
:: -7(2y+11)-2y=-13
:: (3,-4)
:: -16y=64
:: x-2y=11 -> 2y+11
:: -16y - 77 = -13
:: -14y - 77 - 2y = -13
:: x = 2(-4) +11 x=3
1 answer